Asupan protein dan fosfor, rasio fosfor-protein, dan kadar fosfor darah pada pasien gagal ginjal kronis dengan hemodialisis - Ahmad Syauqy; Susetyowati .; Suhardi . (Jurnal Gizi Klinik Indonesia, 2012)
Background: Hyperphosphatemia has become one of the main causes of death in CKD patients on HD. Thus, correction and prevention of hyperphospatemia is a major component in the management of HD patients. High protein diet in HD patients may lead to increased serum phosphate level due to mineral metabolism disorder associated with decreased glomerular filtration rate. In addition, high protein intake often followed by high phosphate intake as high protein foods also contains high phosphate and may cause hyperphosphatemia. Meanwhile, reduction of protein intake to control phosphate level was associated with decreased health and nutritional status in CKD patients. Therefore, appropriate phosphate-protein ratio is essential to provide adequate protein intake and avoid hyperphosphatemia.Objective: To investigate the association between protein and phosphate intake, phosphate-protein ratio and blood phosphate level in CKD patients on routine HD.Method: The study used an analytic observational method with cross sectional design. There were 100 subjects involved in this study. Subject characteristics, protein and phosphate intake, phosphate-protein ratio and intake of phosphate binders were obtained through interview and 3 x24 hour food record. Serum phosphate level was analyzed by inorganic phosphorus quantification method. Food processor was used to analyze the intake of protein and phosphate. Bivariate and multivariate tests with 95% confidence interval were used to analyze the data.Results: Adequate protein intake was observed among 38% subjects, while 46% of them have excess phosphate intake.High phosphate-protein ratio was found in 20% subjects. Most subjects did not take phosphate binders regularly (61%) and have hyperphosphatemia (66%). The average protein intake, phosphate intake, phosphate-protein ratio, and blood phosphate level were 1.1 g/kg/d, 13.5 mg/kg/d, 12.8 mg/g, and 5.6 mg/dl, respectively. Bivariate test showed that there was a significant association between protein intake (p=0.037; RP=2.78), phosphate intake (p=0.005; RP=3.54), phosphate-protein ratio (p=0.045; RP=3.85), and blood phosphate level in CKD patients on routine HD. Multivariate analysis revealed that high phosphate intake and did not consume phosphate binders regularly  were risk factors of hyperphosphatemia (p=0.000; OR=6.543; CI 95%:2.357-18.164 dan p=0.024; OR=3.413; CI 95%:1.179; R2=0.42).Conclusion: Consumtion of low phosphate foods and phosphate binders may reduce the risk of hyperphosphatemia in CKD patients on routine HD.